Alles kann, nichts muss?! Theorien der Modalität bei G. W. Leibniz, D. Lewis und A. Plantinga und ihre Vereinbarkeit mit Spielarten des Theismus - Propach, Jan Levin (Aschendorff Verlag, 2020)
Can God do what He wants or does God want what is in accordance with His very own nature? Is God bound by necessary principles or is necessary what God decrees? Such questions about the relationship between modalities and concepts of God are part of innumerable debates and reach far into the history of philosophy and theology. This study first examines the modal metaphysics of G.W. Leibniz's, D. Lewis' and A. Plantinga's metaphysics together with their very different ontological frameworks. Subsequently, the different forms of theism within contemporary debates within Analytic Philosophy are analyzed: classical and personal theism and panentheism. The heart of this study will be the analysis of the consistencies and inconsistencies that appear when, for metaphysical and ontological reasons, one wants to connect the different forms of theism with the modal theories of Lewis, Leibniz, or Plantinga.